2021
DOI: 10.17977/um001v6i22021p080-089
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience Belief System: A Phenomenological Study on Javanese and Sundanese Family

Abstract: The purpose of this study was to determine family resilience based on the belief system in families with Javanese and Sundanese cultural backgrounds. The method used in this study is a qualitative phenomenological method. Phenomenological studies are used to understand phenomena at the level of subjective reality. Respondents in this study were five families with Javanese ethnic background domiciled in Kebumen and Banyumas regencies, Central Java and three families with Sundanese cultural background domiciled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The Alternative Seat Position of Counselor with the surrounding society. However, optimum development of identity relies on great family relations and friendship (Branje, 2022;Munawaroh et al, 2021).…”
Section: The Alternative Seat Position Of Counselormentioning
confidence: 99%
See 1 more Smart Citation
“…The Alternative Seat Position of Counselor with the surrounding society. However, optimum development of identity relies on great family relations and friendship (Branje, 2022;Munawaroh et al, 2021).…”
Section: The Alternative Seat Position Of Counselormentioning
confidence: 99%
“…Studies have confirmed that the authentic cultures can extend the positive dimension (identity, tradition, and spirituality) of adolescents (Snowshoe & Crooks, 2017), primarily in the collectivist culture that tends to pursue the social happiness, such as in the Asia region (Ford et al, 2015), including in Indonesia. In Indonesia, the people from Sunda and Java tribes have a positive perspective and religious dimension in interpreting life (Munawaroh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%